Synergistic combination of visual features in vision–taste crossmodal correspondences - Lee, BP; Spence, C (Brill, 2023)
There has been a rapid recent growth in academic attempts to summarise, understand, and predict the taste profile matching complex images that incorporate multiple visual design features. While there is now ample research to document the patterns of vision–taste correspondences involving individual visual features (such as colour and shape curvilinearity in isolation), little is known about the taste associations that may be primed when multiple visual features are presented simultaneously. This narrative historical review therefore presents an overview of the research that has examined, or provided insights into, the interaction of graphic elements in taste correspondences involving colour, shape attributes, texture, and other visual features. The empirical evidence is largely in line with the predictions derived from the proposed theories concerning the origins of crossmodal correspondences; the component features of a visual stimulus are observed to contribute substantially to its taste expectations. However, the taste associated with a visual stimulus may sometimes deviate from the taste correspondences primed by its constituent parts. This may occur when a new semantic meaning emerges as multiple features are displayed together. Some visual features may even provide contextual cues for observers, thus altering the gustatory information that they associate with an image. A theoretical framework is constructed to help more intuitively predict and conceptualise the overall influence on taste correspondences when visual features are processed together as a combined image.